First report of Neoechinorhynchus (Acanthocephala: Neoechinorhynchidae) from marine fish of the eastern seaboard of Vietnam, with the description of six new species - Amin O.M.; Ha N.V.; Ha D.N. (Parasite, 2011)
The occurrence of acanthocephalans of the genus Neoechinorhynchus Stiles and Hassall, 1905 in Vietnamese waters is reported for the first time. Six new species are described from seven species of marine fish of the families Belonidae, Clupeidae, Megalopidae, Mugilidae, and Sciaenidae, collected in Halong Bay of the eastern seaboard of Vietnam in 2008 and 2009. These are Neoechinorhynchus (Neoechinorhynchus) plaquensis n. sp. characterized by dermal plaques covering the entire trunk; Neoechinorhynchus manubriensis n. sp. with very long anterior proboscis hooks having roots with prominent anterior manubria and very small and equal middle and posterior hooks, two pseudoretractors in the receptacle, simple vagina, and terminal gonopore; Neoechinorhynchus pennahia n. sp. with equal anterior and middle proboscis and somewhat smaller posterior hooks, and terminal female gonopore; Neoechinorhynchus ampullata with many giant nuclei in the body wall and lemnisci and a parareceptacle structure complex which includes pumping ampullas reported for the first time; Neoechinorhynchus (Neoechinorhynchus) longinucleatus n. sp. with very long giant nuclei in the Lemnisci, anteriorly twisted vagina, and subterminal female gonopore. Neoechinorhynchus (Neoechinorhynchus) ascus n. sp. is the second species of Neoechinorhynchus found with the parareceptacle structure/ampulla complex. Neoechinorhynchus (Neoechinorhynchus) johnii Yamaguti, 1929 of Bilqees, 1972 is not N. johnii because of proboscis armature and other discrepancies with the Yamaguti material. Notes on host distribution and feeding habits are also included.